Computing Tools in an Advanced Filter Theory Course - S. Hossein Mousavinezhad; Stuffle, R Eugene; Pan, Wei; Steven Grant Maclure (Association for Engineering Education - Engineering Library Division Papers, 2014)
Computing Tools in an Advanced Filter Theory Course ABSTRACTSignal processing is an important subject in engineering and computer science disciplines. Fromstudents perspective most concepts of frequency transformation, various transform techniques,impulse response and analog/digital filter design and implementation are considered abstractionsand difficult to understand. To help students visualize difficult concepts in these courses and alsoaiding in computation and analysis of high order systems, several computational tools areavailable as software packages. In this paper we will present details of a senior-level, first yeargraduate course on signal processing where students have access to a design automation softwaretool accompanying a textbook as well as use of commercial tools such as MATLAB,MATHCAD and Pspice. In addition to lecture course there is a separate laboratory section wherestudents experiment with hardware as well as software tools.The textbook software is a filter design/analysis tool, fully functional Windows-based filterdesign software package; it comes with its documented source code detailing the intricacies ofanalog/digital filter design. The software automates the design process and provides filtercoefficients and frequency response characteristics, pole-zero diagrams, and other features aswell. In addition, for analog filters, the Pspice circuit file can be generated to aid in the analysisof active filters. Digital filters designed may be used to filter wave files. After specifying aninput wave file, a filtered output file can be generated, and both input and output files can beplayed using the computer sound card.In studying digital filter design and implementation students need to understand the theorybehind analog filters and their implementation using, for example, active filters. The other kindof digital filter design involves the use of various window functions including the Kaiser windowwhich includes the use of modified Bessel functions. An algorithm is introduced in the course forthe approximation of these high level functions. After “paper” design by students, they can checktheir design computation by using either the software which is part of the book or other availablepackages in the laboratory (we have licenses for both MATLAB and MATHCAD.) It isimportant to realize that for very high order filters, for example designing band-pass filters bytransforming a prototype, normalized low-pass filter, the final design may be of very high order,this will be the case for both analog as well as digital filters. In these high-order systems thecomputation of pole-zero location can result in errors even if a commercial software package isused. The conclusion is that the student should be familiar with both theoretical and practicalaspects of the subject under study. Many engineering educators are facing the problem of righttime, right place and appropriate use of information technology tools that are readily becomingavailable in many courses in engineering and science.